The Effects of Resistance Exercise Training on Strength and Functional Tasks in Adults With Limb-Girdle, Becker, and Facioscapulohumeral Dystrophies - Bostock, Emma L.; O'Dowd, Dawn N.; Payton, Carl J.; Smith, Dave; Orme, Paul; Edwards, Bryn T.; Morse, Christopher I. (Frontiers in Neurology, 2019)
Background The inclusion of resistance training in the treatment and management of muscular dystrophy has previously been discouraged, based on mainly anecdotal evidence. There remains a lack of experimental investigation into resistance training in individuals with muscular dystrophy. The aim of the current study was therefore, to determine the effect of a twelve-week resistance training programme on muscle strength and functional tasks in ambulatory adults with muscular dystrophy. Methods Seventeen ambulatory adults with muscular dystrophy (Facioscapulohumeral muscular dystrophy: n=6, Limb-Girdle muscular dystrophy: n=6, Becker muscular dystrophy: n=5) were recruited for this study. Participants attended three testing sessions: one session at baseline, one session after a twelve-week control period and one session after a twelve-week resistance training period. Each testing session consisted of measurements of isometric knee extensor and knee flexor maximum voluntary contraction (MVC) torque (Cybex dynamometer) and a 6-minute walk test. Participants also completed a timed sit-to-stand, a four steps-stair ascent, and a four steps-stair decent. The twelve-week resistance training period consisted of two supervised sessions a week. Each training session included a 5-minute warm-up, a step-up exercise, free-standing or assisted squats, knee flexion and knee extension exercises, and an additional 6 single-joint exercises specific to each individual’s needs. Results Knee flexor MVC torque increased by 13% after the twelve-week resistance training programme (p < 0.05), with no change over the control period. Knee extensor MVC torque did not significantly change after the training programme or the control period. Time taken to complete sit-to-stand, stair ascent and stair descent all decreased (improved) following the twelve-week training programme (p < 0.05). Six-minute walk distance increased (improved) by 4% after the resistance training period. Conclusions A twice-a-week, twelve-week, resistance training programme resulted in increased knee flexion strength and improvements in functional tasks in ambulatory adults with muscular dystrophy. This provides support for the inclusion of resistance training in the treatment programmes for these forms of muscular dystrophy.